Solid‐Phase Synthesis of Fluorinated Analogues of Glycosyl 1‐Phosphate Repeating Structures from Leishmania using the Phosphoramidite Method. Issue 6 (30th April 2018) - Hara, Rintaro Iwata; Yaoita, Aya; Takeda, Katsuya; Ueki, Hiroaki; Ishii, Ayumu; Imoto, Hideyuki; Kobayashi, Satoshi; Sano, Michi; Noro, Mihoko; Sato, Kazuki; Wada, Takeshi
Abstract: Bacterial and protozoan sugar chains contain glycosyl 1‐phosphate repeating structures; these repeating structures have been studied for vaccine development. The fluorinated analogues of [β‐Gal‐(1→4)‐α‐Man‐(1→6)‐P‐] n, which are glycosyl 1‐phosphate repeating structures found in Leishmania, were synthesised using the solid‐phase phosphoramidite method. This method has been less extensively studied for the synthesis of glycosyl 1‐phosphate units than H ‐phosphonate chemistry. A stepwise synthesis of a compound containing five such repeating units has been conducted using the phosphoramidite method herein, which is the longest glycosyl 1‐phosphate structures to be chemically constructed in a stepwise manner. Abstract : Step by step : A solid‐phase phosphoramidite method was employed for the synthesis of a series of compounds containing [β‐Gal‐(1→4)‐α‐ManF‐(1→6)‐P‐]5 . These compounds are, to our knowledge, the longest glycosyl 1‐phosphate repeating units to be chemically synthesised in a stepwise manner reported to date.